PEMETAAN PERUBAHAN TINGKAT KUALITAS PERMUKIMAN DI KECAMATAN LIMA PULUH, KOTA PEKANBARU - Khofifah, Siti (JURNAL BUANA, 2026)
The objectives of this research are (1) to identify changes in residential areas in the Lima Puluh District and (2) to determine where the highest changes in residential quality levels occurred in 2010 and 2020 in the Lima Puluh District.The research method used is the interpretation of high-resolution imagery and a scoring system for residential quality parameters using GIS software and applying the overlay technique to determine the residential quality levels.The results of this research indicate that the expansion of residential areas from 2010 to 2020 increased by 30.24 hectares. The residential quality in 2010 was categorized into 4 classes: poor quality with an area of 16.47 hectares, less good quality with an area of 221.24 hectares, fairly good quality with an area of 238.98 hectares, and good quality with an area of 46.75 hectares. For the year 2020, the residential quality was categorized into only 2 classes, but there were significant changes: fairly good quality with an area of 463.27 hectares, and good quality with an area of 52.62 hectares.